Analysis of international publications on agricultural biology on the web of science database: current situation and solutions - Phuong, Nguyen Thi; Hue, Dang Thi Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
This article is studied based on Web of Science’s database for Vietnamese authors’ articles in agricultural biology; the use of scientific bibliographic measurement method which is the basis for proving that the analytical data related to quantity and quality in Vietnam’s international publications from 2000-2019* is reliable. This is the first time, a complete set of data on the situation of the international publication WoS is detail analyzed for AB sector funding in different angles. The results of preliminary analysis show that the number of international publications in the agricultural biology sector in the 2000-2019 period * increased sharply from 78 publications in 2000 to 6,895 publications in 2019*. The habit of international publication has many changes in the recognition of sponsorship information. Before 2009, 84% of the publications did not state funding sources, but after 2010, this rate dropped to only 30%. International cooperation in research proves that in order to improve the quality of scientific research in Vietnam, it is necessary to have national cooperation. The research also shows that the great transformation in science and technology human resources (S&T), the participation of the National Foundation for Science and Technology Development in funding and supporting basic research activities has had many positive effects, not only does it increase the number of authors whose Vietnamese address plays a key role in international publications, but also increases the number of authors in a publication. With the results obtained, the study will be useful information proposing solutions to improve the quality of basic research funding for the SOE industry in particular and in basic research finance management in general in Vietnam. Code: 20072301